Determination of Tuberculosis and Tobacco Smoking, Smoking Cessation Care in TB Smokers - Perriot, Jean; Nguyen, Lan Tien; Peiffer, Gérard; Underner, Michel (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Tuberculosis (TB) and tobacco smoking are two major public health problems worldwide causing a high mortality. Tobacco smoke increases the risks of Mycobacterium tuberculosis infection, development for pulmonary and extrapulmonary TB, of severe forms of the disease and death from TB, smokers with TB are less compliant with TB medications. The risk of TB increases in people who smoke more and who smoked for a long time. Smoking cessation interventions help TB smokers to quit and reduces the impact of tobacco use on the course of the disease. Stopping smoking increases adherence to TB treatment and contributes to control epidemic in emerging countries. Smoking cessation interventions are effective in TB smokers and require the involvement of healthcare professionals.